Actual Problems of Virtual Reading - Uzakov Kakhramon (Researchparks Publishing, 2022)
This article describes the theoretical aspects of virtual reading, its role in people's lives today and the impact of social networks, as well as the existing opportunities in this area, the analysis of the attitude of civil servants and educators to virtual reading.